Playing It Safe with Play Equipment - Donna Davis (EDIS, 2012)
“Raising my rough-and-tumble children at times took superhuman energy, patience, and constant supervision. Even the joyful vision of a playground could be daunting when the swing was used as a human slingshot and the slide had 101 uses, of which only one was acceptable. I’m sure many parents can relate to the fear of the unknown dangers on the playground.” This 2-page Family Album Radio transcript was written by Donna Davis and published by the UF Department of Family, Youth and Community Sciences, July 2012.